FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU MEROKOK PADA ATLET BASKET PUTRA UNIVERSITAS X DI KOTA SEMARANG - Ina Viernisa Febrina; Kusyogo Cahyo; Suroto Suroto (Jurnal Kesehatan Masyarakat (Undip), 2016)
The researcher found that the percentage of X University basketball athlete in Semarang who smokes reached to 70%. The purpose of this study is to analyze the factors related to smoking behavior on male basketball athletes of X University in Semarang city. This study is a quantitative research using cross sectional approach. The population of this study is the members of Basketball Student Interests Unit of X University in Semarang with 50 persons as samples in the total number using total sampling method. The data analyses used in this study are univariate and bivariate statistical test analysis of Chi Square (significance level of 0.05). Most of the respondents were 17-25 years of age (the last level of teens) are 96.0%. About 62,0% of respondents’ parents occupations are entrepreneur and about 80,0% of the respondents are having smoking family member more than one person. The respondents’ knowledge in high categories are 72,0%, perceived susceptibility (54.0%), perceived seriousness (70.0%), perceived benefits (70.0%), perceived barrier (48.0%), cues to action (50.0%), and VO2max low category (32.0%). Chi-Square test results found that there is a relationship between the number of smokers in a family, knowledge, perceived susceptibility, perceived benefits, and VO2max. While related to the age, perceived seriousness, perceived barriers, and cues to action found that there is no relationship toward basketball athlete of X University smoking behavior. Chi Square test results found that there is no relationship between the parents’ occupations.